The role of leadership and work motivation on job satisfaction according to the view of PT Indomarco Prismatama Employees - Abdullah, Abdullah; Magfirotulhayat, Magfirotulhayat; Rosiana, Safitri; Haryadi, Didit (Junal Ilmu Manajemen, 2024)
Effective management, thinking about the importance of human resources. Employee job satisfaction is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee job satisfaction and develop a theoretical basis and research model. This study used the associative descriptive quantitative method with a population of 40 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee job satisfaction is influenced by leadership style; the more influential the leader is in making decisions, the more employee job satisfaction increases. The second hypothesis states that work motivation affects employee job satisfaction. The third hypothesis is that employee performance is influenced by leadership style and employee work motivation, which can simultaneously increase employee job satisfaction. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.